2014
DOI: 10.1038/nmat3941
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolving valley quantum interference of a donor in silicon

Abstract: Electron and nuclear spins of donor ensembles in isotopically pure silicon experience a vacuum-like environment, giving them extraordinary coherence. However, in contrast to a real vacuum, electrons in silicon occupy quantum superpositions of valleys in momentum space. Addressable single-qubit and two-qubit operations in silicon require that qubits are placed near interfaces, modifying the valley degrees of freedom associated with these quantum superpositions and strongly influencing qubit relaxation and excha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
187
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(208 citation statements)
references
References 61 publications
(138 reference statements)
15
187
4
2
Order By: Relevance
“…Recent transport spectroscopy studies of an individual acceptor embedded in nano-scale transistors have shown that for acceptors ∼10 nm away from an interface the bulk-like four-fold degeneracy is maintained [8]. Here we demonstrate that the presence of a nearby interface (<2 nm) lifts the four-fold degeneracy of the acceptorbound hole ground state by investigating the energy spectrum and wavefunctions of individual sub-surface boron acceptors using scanning tunnelling spectroscopy (STS).Recent low-temperature STM/STS studies have successfully probed the energy spectrum and wavefunctions of individual impurity atoms in Si [9][10][11] and GaAs [12,13]. These studies have revealed the influence of the semiconductor/vacuum interface on the ionization energy of sub-surface dopants [9,13], the spatially resolved structure of the dopant wavefunction [10][11][12] and the mechanisms for charge-transport through these dopants [9,11,14].…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Recent transport spectroscopy studies of an individual acceptor embedded in nano-scale transistors have shown that for acceptors ∼10 nm away from an interface the bulk-like four-fold degeneracy is maintained [8]. Here we demonstrate that the presence of a nearby interface (<2 nm) lifts the four-fold degeneracy of the acceptorbound hole ground state by investigating the energy spectrum and wavefunctions of individual sub-surface boron acceptors using scanning tunnelling spectroscopy (STS).Recent low-temperature STM/STS studies have successfully probed the energy spectrum and wavefunctions of individual impurity atoms in Si [9][10][11] and GaAs [12,13]. These studies have revealed the influence of the semiconductor/vacuum interface on the ionization energy of sub-surface dopants [9,13], the spatially resolved structure of the dopant wavefunction [10][11][12] and the mechanisms for charge-transport through these dopants [9,11,14].…”
mentioning
confidence: 77%
“…These studies have revealed the influence of the semiconductor/vacuum interface on the ionization energy of sub-surface dopants [9,13], the spatially resolved structure of the dopant wavefunction [10][11][12] and the mechanisms for charge-transport through these dopants [9,11,14]. Here, we use STS to measure the energy difference between the heavy-hole and light-hole states of individual B acceptors less than 2 nm away from the surface.…”
mentioning
confidence: 99%
“…In this work, we use a large-scale atomistic tight-binding method that describes the crystal as a linear combination of atomic orbitals, and captures the full-energy spectrum of a donor in silicon, including the conduction band valley degrees of freedom, the valley-orbit interaction, 24 the Stark shift of the donor orbitals, 18 and real and momentum space images of the donor obtained by scanning tunnelling microscope experiments. 25 Using the atomistic wavefunctions, we compute the two-electron states of donor and donor clusters in the presence of an electric field from an FCI technique. The same method has been successful in solving the challenging problem of the D − state (the two-electron state of a single donor) without any fitting parameters and providing a charging energy of 45 meV (ref.…”
Section: Methodsmentioning
confidence: 99%
“…1(b 13,14,21 , which inherently incorporates the valley-orbit (VO) interaction in order to correctly capture the atomic fine detail for both P and As cases. As the dopants are close to the surface, the effects of dimer formation (2×1 reconstruction) 12,22 and hydrogen passivation 23 are included in the tight-binding Hamiltonian (supplementary section S2).…”
Section: Quantum Treatment Of Stm Measurementmentioning
confidence: 99%
“…The technique involves low temperature STM imaging 12 in conjunction with a fully quantum, large-volume treatment of the STM-dopant system. We demonstrate the metrology procedure using STM images obtained for several sub-surface P and As dopants.…”
mentioning
confidence: 99%